Extension for Community Healthcare Outcomes Based Telementoring of Physicians for Dementia–Effectiveness in India - Nair, Shruti; Sinha, Preeti; Chand, Prabhat; Sahu, Prashant; Gorthi, Naga VSS; Varghese, Mathew; Sivakumar, P. T. (Frontiers in Psychiatry, 2022)
Objective: The study aimed to evaluate the effectiveness of a program based on the telementoring model (Extension for Community Healthcare Outcomes (ECHO)) for primary care physicians in diagnosing and treating patients with dementia. Method: The ECHO model was adapted through 10 hours of self-paced e-learning, interim assignments, and 12 live sessions of 2 hours every 2 weeks consisting of a didactic presentation by the expert and peer-led case discussion. Impact was examined by noting participation, session ratings, monthly clinical reports, and comparing knowledge and competency scores before and after the course. Results: Among the 63 participants, 39.7% attended at least 80% of the sessions; completing the program successfully. The ratings for all sessions were in the range of good to excellent. The paired sample t-test revealed a statistically significant improvement (p <0.001) in self-rated skills and confidence in diagnosing and treating dementia with an effect size of 1.25 and 1.37, respectively. No change in knowledge score was observed throughout the course. A considerable increase in dementia related clinical practice was observed during 4 month summary of clinical cases. Due to limited data from monthly reports during the COVID pandemic, no statistical analysis was attempted. Conclusions: The ECHO model appears to have a positive immediate impact on the clinical ability of primary care physicians to diagnose and treat dementia. Its direct impact on patient health and at the community level should be aimed in future studies.